Identification of Puputan Badung Field as a Family Tourism Attraction in Denpasar City Bali - Widiantara, I Gusti Agung Bagus; Wirya, I Made Suwitra; Darma Susila, I Made Gede (Jurnal Manajemen Pelayanan Hotel, 2023)
The people of Denpasar City and its surroundings need green open space to release fatigue after busy activities. One of these open spaces is obtained at Puputan Badung I Gusti Ngurah Made Agung Field which has tourism potential both natural, historical, cultural and man-made tourism to continue to be developed into a family tourist attraction in Denpasar City, Bali. The existence of this field is supported by various parties, both local communities, tourists to the Denpasar City Government with the existence of Denpasar City Regional Regulation Number 3 of 2019 concerning the Regional Tourism Development Master Plan for 2018-2029. The tangible manifestation of the role of the Denpasar City government to realize Puputan Badung Field as a Family Tourism Attraction is reflected in the existence of 4A elements (attraction, Atraction, Amenity, Accessibility, and Ancillary) that are adequate to date. In this study, data collection was carried out by means of literature studies, documentation and observation. The data analysis technique is carried out using the qualitative descriptive method. The results of this research, it can be concluded that Puputan Badung I Gusti Ngurah Made Agung Field meets the needs of the community for family tourism attraction. Keywords: Identification, Puputan badung field, Family tourism attraction.